Carpooling: User Profiles and Well-being - Lucía Echeverría; J. Ignacio Gimenez-Nadal; José Alberto Molina (Institute of Labor Economics (IZA), 2021)
Carpooling is a sustainable daily mobility mode, implying significant reductions in energy consumption and CO2 emissions, although it remains an uncommon practice. With the aim of stimulating this green transportation mode, this paper focus on understanding why certain individuals will agree to share a car to a common destination, apart from the obvious environmental benefit in emissions. It first describes the profile of users and then explores the relationship between this transportation mode and the participants' well-being. To that end, we have selected two countries, the UK and the US, where the use of cars represents a high proportion of daily commuting. We use the UK Time Use Survey (UKTUS) from 2014-2015 and the Well-Being Module of the American Time Use Survey (ATUS) from 2010-2012-2013 to identify which groups in the population are more likely to pool their cars, and with whom those individuals enjoy carpooling more. Results indicate that individuals with certain socio-demographic characteristics and occupations are more likely to commute by carpooling, but the profile seems to be country-specific. Furthermore, our evidence reveals a positive relationship between carpooling and well-being during commuting.
Keywords: R40; J22; 330; carpooling; green mobility; user profiles; subjective well-being